Hybrid-virtual simulations for Canadian medical students during the COVID-19 pandemic - Riley Reel; Kevin Gunther; Samuel Kirk; David Landells; Anne Theilmann; Morgan Haines (Canadian Medical Education Journal, 2021)
Implication Statement: